Two way power flow in advance distributions and micro grid - Kamarudin, Mohd Khairul Shazril (2013)
The Power Flow is most important issue to ensure an efficient yet affordable system. To maintain a low failure electrical breakdown or blackout times can be too subjective if a new approaches or solution and idea is never be made to improve it. Nowadays, a Two Way Power Flow has played a big role in this issue. One day, a retro and old technique generation in example coal-fired generator that used by IPP (Independent Power Plant) or TNB is not to be available anymore due to its difficulty to find a raw material. An alternative ways has been come out through the global IEEE conferences worldwide and a replacement and suggestion of renewable energy being a good solution to overcome this problem. With this two way power flow or known as bidirectional power flow, an advanced and complex system will be introduced. Main consideration to focus is totally based on the electrical equipments and power cables. Transformers would having a problem to adopt this scenario since it only capable to do 1 way power flow either step up to step down or step down to step up voltage. The objective of the project is to perform simulation via PSSE and analysis the data via MATLAB for Two Way Power Flow In Advance Distributions and Micro-Grid. This project aim is to apply concept of Two Way Power Flow in a real case with an additional of Micro-Grid in the system. In this thesis, there will be further explanation about Advance Distribution, Micro-Grid, Renewable Energy, Distributed Generator (DG), Electrical devices and Voltage stability.